Development of colorimetric method for cephalexin in dosage forms - Priyanka, P; Suresh1, P (Asian Journal of Pharmaceutics (AJP), 2014)
Asimple, sensitive, accurate, rapid, and economical colorimetric-spectrophotometric method has been developed for the estimation of cephalexin in capsules. This method is based on the reaction of the drug with ferric chloride and potassium ferricyanide, giving a green-colored chromogen exhibiting maximum absorbance at 791 nm against reagent blank. Beer’s law was obeyed in the concentration range of 1-6 μg/ml. Results of the analysis were validated statistically and by recovery studies.